Use of Accurate V3 software as an introduction to accounting skills in “Merdeka Belajar Kampus Merdeka” Program - Retna Safriliana; Diyah Sukanti Cahyaningsih; Parawiyati Parawiyati (University of Merdeka Malang, 2021)
In supporting the student exchange program at the national Program